BUDAYA ORGANISASI, KEPUASAN KERJA DAN KARAKTERISTIK PENGARUHNYA TERHADAP KOMITMEN ORGANISASIONAL (pada Karyawan KOP “SAE” Pujon Malang Jawa Timur) - Ulya Munzilatul Qushwa; Hadi Sunaryo (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT                             At present, an organization needs human resources. Therefore an organization always increases organizational commitment and various ways are carried out by the organization to find out the factors that cause a decrease or increase in organizational commitment. The purpose of this study is to analyze organizational culture, job satisfaction and individual characteristics of organizational commitment. The research object chosen in this study was the Pujon Malang "SAE" cooperative. Data was collected through a questionnaire method that was filled out by 77 respondents using the census method. The results of this study conclude that (1) organizational culture does not have an important impact on organizational commitment, (2) job satisfaction has an important impact on organizational commitment, and (3) individual characteristics have an important impact on organizational commitment